Poetics of Music in the Form of Six Lessons - Stravinsky, Igor 1882-1971; Knodel, Arthur; Dahl, Ingolf 1912-1970 (USA Harvard university press, 1947)
One of the greatest of contemporary composers has here set down in delightfully personal fashion his general ideas about music and some accounts of his own experience as a composer. Every concert-goer and lover of music will take keen pleasure in his notes about the essential features of music, the process of musical composition, inspiration, musical types, and musical execution. Throughout the volume are to he found trenchant comments on such subjects as Wagnerism, the operas of Verdi, musical taste, musical snobbery, the influence of political ideas on Russian music under the Soviets, musical improvisation as opposed to musical construction, the nature of melody, and the function of the critic of music. Musical people of every sort will welcome this first presentation in English of an unusually interesting book.
Keywords: Music criticism